(untitled) (Research, Society and Development, 2023)
Researches on renewable energies aims to reduce or replace fossil fuels, responsible for the emission of greenhouse gases. Another environmental problem is the improper disposal of livestock waste. Therefore, the objective of this research is the production of biogas using these residues, promoting an alternative energy source, in addition to generating biofertilizer for rural producers. Three anaerobic digesters were developed; fed with pig manure (BS), poultry manure (BA), and a binary mixture - with pig and poultry manure (BB). Biogas production and composition, temperature parameters, pH, total, fixed and volatile solids were determined. The BS showed greater production of biogas and methane in relation to volatile solids (SV) reduced from the total volume, which was 804.8 L/kg SV of biogas and 572.2 L/kg SV of methane. Followed by BB with 626.0 L/kg SV of biogas and 457.6 L/kg SV of methane, and the lowest values for BA with 522.8 L/kg SV of biogas and 259.4 L/kg SV of methane. The media synthesized with biofertilizers were efficient in microalgae cultivation. The purification of biogas in the cultivation of Chlorella sp. presented removal from 20.5±1.6 to 53.8±3.3% depending on the concentration of CO2 in the biogas, increasing the calorific value. in addition to increasing the concentration of algal biomass and the content of PT, CT and LT in the cultivation in relation to the control assay. Evidencing the great potential for biogas generation by biodigesters using livestock waste and microalgae production with the synthesized means.